TRANSFORMASI KEAGAMAAN MASYARAKAT MUALAF DUSUN KALA DESA WIH ILANG KECAMATAN PEGASING KABUPATEN ACEH TENGAH - Nurul Qomariyah Ahmad; Suminah; Ruri Amanda (Asosiasi Dosen Perguruan Tinggi Islam, 2020)
Abstract: The mualaf community of Kala Hamlet, Wih Ilang Village , Central Aceh Regency, Aceh Province, embraced Islam simultaneously and massively. They are Karo Catholics who previously lived in the Karo District of North Sumatra Province. One of the reasons for the transfer of the Karo community to the Kala hamlet was to make a living. The transfer process has been going on since the 1990. It takes process and effort to become a good Muslim. The purpose of this research is to know the religious transformation in the field of worship. This research uses descriptive qualitative with in-depth interview techniques, FGD, documentation and observation. The validity of the data uses triangulation techniques with Milles and Hubberman analysis . Based on the results of the study, it was found that the converts of the people of Kala underwent a process of transforming religious life in the field of worship by committing to perform worship according to Islamic teachings properly and correctly , despite the limited conditions and constraints when embracing Islam had been 30 years old . thus causing them to experience delays in understanding the Koran reading and prayer reading in worship rituals. In addition there are still many practices of compassion that they have not yet understood and will result in suboptimal levels of worship. Keywords: Transformation, Religious, Mualaf Abstrak: Masyarakat mualaf Dusun Kala Desa Wih Ilang Kabupaten Aceh Tengah, Provinsi Aceh memeluk agama Islam secara serempak dan masif. Mereka merupakan keturunan suku Karo beragama Katholik yang sebelumnya berdomisili di Kabupaten Karo Provinsi Sumatera Utara. Salah satu alasan perpindahan masyarakat Karo tersebut ke Dusun Kala untuk mencari penghidupan. Proses perpindahan sudah berlangsung sejak tahun 1990-an. Dibutuhkan proses dan usaha agar menjadi seorang Muslim yang baik. Tujuan dari penelitian ini mengetahui transformasi keagamaan pada bidang ibadah. Penelitian ini menggunakan kualitatif deskriptif dengan teknik wawancara mendalam, FGD, dokumentasi dan observasi. Keabsahan data menggunakan teknik triangulasi dengan analisis Milles and Hubberman. Berdasarkan hasil penelitian didapatkan bahwa masyarakat mualaf Dusun Kala menjalani proses transformasi kegamaan pada bidang ibadah dengan berkomitmen menjalankan ibadah sesuai ajaran Islam secara baik dan benar, walaupun kondisi yang terbatas serta mengalami kendala ketika memeluk agama Islam sudah berusia 30 tahun. sehingga menyebabkan mereka mengalami keterlambatan dalam memahami bacaan Alquran maupun bacaan doa dalam ritual ibadah. Selain itu masih banyak praktik ibadah yang belum mereka pahami dan akan berakibat tidak optimalnya tataran ibadah. Kata Kunci: Transformasi, Keagamaan, Mualaf